ANALISIS PENGARUH NET INTEREST MARGIN (NIM) DAN BIAYA OPERASIONAL DAN PENDAPATAN OPERASIONAL (BOPO) TERHADAP RETURN ON EQUITY (ROE) PADA PT. BANK PERMATA, TBK - Nur Iklimah; Nurul Huda; M. Rimawan (CV. Denasya Smart Publisher, 2025)
This study aims to determine the partial and simultaneous effect of Net Interest Margin and Operating Expense to Operating Income on Return on Equity at PT. Bank Permata, Tbk. This research uses data analysis techniques such as classical assumption tests, multiple linear regression analysis, and hypothesis testing with SPSS Version 24. The results show that Net Interest Margin does not have a partial effect on Return on Equity at PT. Bank Permata, Tbk, while Operating Expense to Operating Income has a partial effect on Return on Equity at PT. Bank Permata, Tbk. Simultaneously, Net Interest Margin and Operating Expense to Operating Income have a significant effect on Return on Equity at PT. Bank Permata, Tbk..